Crohn's disease and ulcerative colitis are associated with the DNA repair gene MLH1. - Pokorny, R M (1997)
OBJECTIVE: The purpose of this study was to determine whether there is an association between Crohn's disease and ulcerative colitis with MLH1. SUMMARY BACKGROUND DATA: Identification of genes involved in the etiology of inflammatory bowel disease may lead to the development of markers that objectively can define disease and permit therapy. The treatment of Crohn's disease of the colon and ulcerative colitis also is complicated by difficulties in differentiating the two conditions. METHODS: The DNA and clinical data were obtained on 126 unrelated individuals (45 Crohn's disease, 36 ulcerative colitis, and 45 control subjects without intestinal disease). Polymerase chain reaction products were analyzed by single-strand conformation polymorphisms (MLH1 exons 9, 11, 14, 15, and 16) and polyacrylamide gel electrophoresis (markers D3S1611 and D3S1768). All comparisons were analyzed by chi square test. The association between single haplotypes and disease was expressed as relative odds. RESULTS: MLH1 exons 9, 11, 14, and 16 were monomorphic. Two, four, and six alleles were detected in MLH1 exon 15, D3S1611, and D3S1768, respectively. Significant associations were observed for MLH1 exon 15/D3S1611 haplotypes AB (OR = 5.5; p = 0.007) and BA (p = 0.002) with Crohn's disease and for haplotypes AB (OR = 4.0; p = 0.042), BA (p = 0.035), and BC (OR = 6.1; p = 0.016) with ulcerative colitis. Family history of inflammatory bowel disease was associated with D3S1768/D3S1611 (p = 0.05) and MLH1 exon 15/D3S1611 haplotypes (p = 0.03). D3S1611/D3S1768 haplotype CD (OR = 11.3; p = 0.03) was associated with disease, whereas MLH1 exon 15/D3S1611 haplotype AA (OR = 0.25; p = 0.02) was protective. Comparisons of MLH1 exon 15/D3S1611 haplotypes of Crohn's colitis and patients with ulcerative colitis were significant (p = 0.037). CONCLUSIONS: This study identifies a novel genetic and clinical association between MLH1 and inflammatory bowel disease.